“Cordel de Saia”: autoria feminina no cordel contemporâneo - Melo, Miriam Carla Batista de Aragão de (2016)
This dissertation proposes to investigate the (in)visibility of the female authorship in the string literature, historically understood as “poetic of men", and discuss tendencies and deadlocks on the building of the gender, analysing in what way these female voices of contemporary string literature put in the spotlight the woman in her poems. Therefore , we elected a corpus formed by three booklets O que é ser mulher?, by Salete Maria, A mulher e sua trilha, by Rosário Pinto and Saias no cordel, by Dalinha Catunda, chosen by criteria of poetic quality, by discusssing processes of (de)construction of the woman in society and by the relation to its authors with the Academy, institution to keep the memory and that contributed to the consolidation of string literature in the national scenery. In the first chapter, we discussed the concepts of literature and culture, and we distinguished historic aspects of string literature. In the second chapter, we stress the acting of string literature women who are skillful in the art of making up stanzas. As for the third chapter, we have discussed issues of gender when we study proposed poems for analysis. In general, this work tries to contribute with a greater difusion of the study of popular culture and the rescue of female voices of string literature, invisible and aphonic socially made, suggesting the opening of possibilities in an effort of reflexion of places of talk in society.